2014
DOI: 10.1021/jp500778w
|View full text |Cite
|
Sign up to set email alerts
|

Coordination versus Solvation in Al+(benzene)nComplexes Studied with Infrared Spectroscopy

Abstract: Singly charged aluminum-benzene cation complexes are produced by laser vaporization in a pulsed supersonic expansion. The Al(+)(benzene)n (n = 1-4) ions are mass selected and investigated with infrared laser photodissociation spectroscopy. Density functional theory (DFT) is employed to investigate the structures, energetics and vibrational spectra of these complexes. Spectra in the C-H stretching region exhibit sharp multiplet bands similar to the pattern known for the Fermi triad of the isolated benzene molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 99 publications
1
19
0
Order By: Relevance
“…Spectroscopic characterization of metal-hydrocarbon radicals or ions formed in gas phase reactions has recently attracted considerable attention. Metal ion-hydrocarbon species are largely investigated by infrared or ultravioletvisible photodissociation or photoelectron spectroscopy, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] whereas metal atom-hydrocarbons are mainly studied by photoexcitation or photoionization techniques. [21][22][23][24][25][26][27][28][29][30][31][32] In principle, spectroscopic measurements could offer detailed information about metal-ligand bonding, molecular structures, and electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic characterization of metal-hydrocarbon radicals or ions formed in gas phase reactions has recently attracted considerable attention. Metal ion-hydrocarbon species are largely investigated by infrared or ultravioletvisible photodissociation or photoelectron spectroscopy, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] whereas metal atom-hydrocarbons are mainly studied by photoexcitation or photoionization techniques. [21][22][23][24][25][26][27][28][29][30][31][32] In principle, spectroscopic measurements could offer detailed information about metal-ligand bonding, molecular structures, and electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…[ 111–113 ] An Al + ‐benzene DFT study shows that the interaction is mostly through cation‐ π electrostatic interactions (charge‐induced dipole), [ 107 ] rather than the covalent bonding that dominates in the case of transition metal‐benzene complexes. [ 107 ] The binding energy of Al + ‐benzene was found to be 30.00 kcal mol −1 at B3LYP/6‐311+G(d,p) and at a distance of 3.005 Å from the center of benzene ring [ 107 ] and 2.756 Å at MP2/6‐311+G*. [ 103 ] Wiberg and Mayer bond orders give values between 0.4 to 0.5 and 0.8 to 0.9 for the AlC bond, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported for the interaction of Al and transition metals with benzene. [102][103][104][105][106][107][108][109][110] This interaction of aluminum with the MOF ring is large based on the literature for the Al-π interaction and compared to the case of Al + -benzene. The experimental binding energy for Al + -benzene is 35.20 kcal mol −1 .…”
Section: Structure Of Doped and Nondoped Irmof-8mentioning
confidence: 99%
“…[42][43][44][45] The difference between the electronic configurations of Al + and V + has been shown to account for their altered coordination number of 3 and 2, respectively, in benzene complexes. 46,47 To observe the stability of the Al + Bz n and V + Bz n clusters, we employed the optional DUV-LIMS to identify clusters, based on their intramolecular noncovalent Bz-Bz or Bz with metal ions (Al + or V + ) interactions. 48,49 We obtained high-resolution mass spectra of benzene clusters up to 30 molecules, on which we introduced Al + or V + by laser ablation of the corresponding metal target by way of molecular beam expansion.…”
Section: Introductionmentioning
confidence: 99%